Síndrome postcolecistectomía y diagnóstico imagenológico - Honores Cajamarca, Karina Elizabeth (Machala : Universidad Técnica de Machala, 2023)
INTRODUCTION: Post-cholecystectomy syndrome is defined as the clinical presentation of abdominal pain at the upper right quadrant, that can be associated but not limited to other gastrointestinal symptoms like nausea, vomiting, diarrhea, and an abdominal lump presence in patients with a recent history of laparoscopic cholecystectomy. AIM: To describe post-cholecystectomy syndrome through the diagnosis aid by imaging tools by means of systematic review of scientific articles published in indexed journals for the comprehensive management of patients in primary health care. METHODOLOGY: Descriptive observational study; scientific articles published in Pubmed, LILACS, Cochrane Library, Science Direct (Elsevier) databases were collected, with the result of 14 articles from the last 5 years and 6 from the last 10 years, to acquire information about post-cholecystectomy syndrome and how imaging studies support their diagnostic suspicion.
El síndrome postcolecistectomía se define como la presentación de dolor abdominal en el hipocondrio derecho, que puede estar asociado o no a náuseas, vómitos, diarrea y sensación de masa en abdomen, en pacientes con antecedente de colecistectomía laparoscópica reciente o incluso de años. OBJETIVO: Describir síndrome postcolecistectomía a través del diagnóstico por imágenes, mediante la revisión sistemática de artículos científicos publicados en revistas indexadas, para el manejo integral de los pacientes en atención primaria en salud. METODOLOGÍA: Estudio observacional descriptivo, se recopilaron artículos científicos publicados en las bases de datos de Pubmed, LILACS, Cochrane Library, Science Direct (Elsiever), con el resultado de 14 artículos de los últimos 5 años y 6 de los últimos 10 años, para extraer información acerca del síndrome postcolecistectomía y cómo los estudios de imagen permiten confirmar su sospecha diagnóstica.
Keywords: VESICULA BILIAR; COLELITIASIS; COLECISTECTOMIA LAPAROSCOPICA